2005
DOI: 10.1039/b419171d
|View full text |Cite
|
Sign up to set email alerts
|

Combination of orthogonal supramolecular interactions in polymeric architectures

Abstract: Supramolecular polymers represent a highly interesting approach towards new "smart materials". A recent strategy includes the combination of different "orthogonal" non-covalent binding sites within one polymer system. Different functionalities can be introduced in a highly defined way by controlled self-assembly processes. This feature article presents highlights in the supramolecular polymer chemistry of multiple hydrogen-bonding, metal complexation (especially of bi- and terpyridines) and host-guest interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
143
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(145 citation statements)
references
References 73 publications
0
143
0
2
Order By: Relevance
“…[42,43] For this proof-ofprinciple study, we selected a preorganized bis-biotinylated terpyridine ligand Biot 2 -terpy that binds to two cis-related sites in streptavidin. [44][45][46][47] A ferrous ion was chosen as terpyridine binds in a cooperative fashion (K 1 = 1.26 10 7 m À1 , K 2 = 6.31 10 13 m À1 ), [48] thus ensuring the exclusive formation of a linear connector bearing four biotin anchors ( Figure 2). Experimental details for the synthesis and the characterization of the [Fe(Biot 2 -terpy) 2 ] 2+ complex are described in the Supporting Information.…”
mentioning
confidence: 99%
“…[42,43] For this proof-ofprinciple study, we selected a preorganized bis-biotinylated terpyridine ligand Biot 2 -terpy that binds to two cis-related sites in streptavidin. [44][45][46][47] A ferrous ion was chosen as terpyridine binds in a cooperative fashion (K 1 = 1.26 10 7 m À1 , K 2 = 6.31 10 13 m À1 ), [48] thus ensuring the exclusive formation of a linear connector bearing four biotin anchors ( Figure 2). Experimental details for the synthesis and the characterization of the [Fe(Biot 2 -terpy) 2 ] 2+ complex are described in the Supporting Information.…”
mentioning
confidence: 99%
“…19 For instance, over the past several years, a huge number of reports on the construction of crosslinked polymers and supramolecular polymers connected by cucurbit[n]urils (especially CB [8]) driven by host-enhanced ππ interaction have been reported by Zhang,20 Scherman, 21 and others. 22 As with the self-sorting studies of CBs, Isaacs and co-workers reported studies on the systematic binding abilities of three members of the CB[n] family (CB[6], CB [7], and CB [8]) toward up to 24 different guests with different structural natures such as size and shape. It was found that the high selectivity between the host and guest molecules would allow for the construction of complex selfsorting systems.…”
Section: Cucurbit[n]uril-based Self-sorted Supramolecular Polymersmentioning
confidence: 99%
“…Thus, some multicomponent supramolecular polymers have been efficiently prepared through this strategy, which displayed tailored chemical and physical properties. Surprisingly, although Schubert et al 7 and Wang et al 8 have presented excellent reviews on the advanced supramolecular polymers constructed from multiple components, the development of supramolecular polymers based on self-sorting hostguest interactions has not been reviewed yet. In this review article, we summarize the recent progress in the construction of supramolecular polymers driven by self-sorting hostguest interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42,43] For this proof-ofprinciple study, we selected a preorganized bis-biotinylated terpyridine ligand Biot 2 -terpy that binds to two cis-related sites in streptavidin. [44][45][46][47] A ferrous ion was chosen as terpyridine binds in a cooperative fashion (K 1 = 1.26 10 7 m À1 , K 2 = 6.31 10 13 m À1 ), [48] thus ensuring the exclusive formation of a linear connector bearing four biotin anchors ( Figure 2 2+ ion and Sav can be conveniently monitored with the disappearance of an induced CD signal, l max = 505 nm, caused by the displacement of 2-(4'-hydroxyazobenzene)benzoic acid (HABA, a hydrophobic dye weakly bound within the biotin-binding pocket) by the [Fe(Biot 2 -terpy) 2 ] 2+ ion (see the Supporting Information). [37,49] Upon standing at room temperature, the dilute purple solution containing the metal + ligand + protein triad slowly becomes turbid, suggesting the formation of polymeric material {[Fe(Biot 2 -terpy) 2 ] 2+ &Sav} 1 .…”
mentioning
confidence: 99%